Exploration of inhibitors of the bacterial LexA repressor-protease. (1st June 2022) - Jaramillo, Ana Victoria Cheng; Cory, Michael B.; Li, Allen; Kohli, Rahul M.; Wuest, William M.
Graphical abstract: Abstract: Resistant and tolerant bacterial infections lead to billions in healthcare costs and cause hundreds of thousands of deaths each year. The bulk of current antibiotic research efforts focus on molecules which, although novel, are not immune from acquired resistance and seldomly affect tolerant populations. The bacterial SOS response has been implicated in several resistance and tolerance mechanisms, making it an attractive antibiotic target. Using small molecule inhibitors targeting a key step in the deployment of the SOS response, our approach focused on preventing the deployment of mechanisms such as biofilm formation, horizontal gene transfer, and error-prone DNA repair. Herein we report the synthesis and testing of analogs of a triazole-containing tricyclic inhibitor of LexA proteolysis, the key event in the SOS response. Our results hint that our inhibitor's may function by adopting a β-hairpin conformation, reminiscent of the native cleavage loop of LexA.